Anterior migration of lateral plate mesodermal cells during embryogenesis of the pufferfish Takifugu niphobles: insight into the rostral positioning of pelvic fins. Issue 1 (28th May 2015) - Tanaka, Mikiko; Yu, Reiko; Kurokawa, Daisuke
Abstract In vertebrates, paired appendages (limbs and fins) are derived from the somatic mesoderm subsequent to the separation of the lateral plate mesoderm into somatic and splanchnic layers. This is less clear for teleosts, however, because the developmental processes of separation into two layers and of extension over the yolk have rarely been studied. During teleost evolution, the position of pelvic fins has generally shifted rostrally (Rosen; Nelson, 1982, 1994), although at the early embryonic stage the presumptive pelvic fin cells are initially located near the future anus region – the anterior border of hoxc10a expression in the spinal cord – regardless of their final destination. Our previous studies in zebrafish (abdominal pelvic fins) and Nile tilapia (thoracic pelvic fins) showed that the presumptive pelvic fin cells shift their position with respect to the body trunk after its protrusion from the yolk surface. Furthermore, in Nile tilapia, presumptive pelvic fin cells migrate anteriorly on the yolk surface. Here, we examined the embryonic development of the lateral plate mesoderm at histological levels in the pufferfish Takifugu niphobles, which belongs to the highly derived teleost order Tetraodontiformes, and lacks pelvic fins. Our results show that, in T. niphobles, the lateral plate mesoderm bulges out as two separate layers of cells alongside the body trunk prior to its further extension to cover the yolk sphere. Once the lateral plate mesoderm extends laterally, it rapidly covers the surface of the yolk. Furthermore, cells located near the anterior border of hoxc10a expression in the spinal cord reach the anterior‐most region of the yolk surface. In light of our previous and current studies, we propose that anterior migration of presumptive pelvic fin cells might be required for them to reach the thoracic or more anterior positions as is seen in other highly derived teleost groups.